6x+11=-3x+16

Simple and best practice solution for 6x+11=-3x+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+11=-3x+16 equation:



6x+11=-3x+16
We move all terms to the left:
6x+11-(-3x+16)=0
We get rid of parentheses
6x+3x-16+11=0
We add all the numbers together, and all the variables
9x-5=0
We move all terms containing x to the left, all other terms to the right
9x=5
x=5/9
x=5/9

See similar equations:

| 608x=20 | | k/−7+2=-5 | | p÷2-(-3)=5 | | 4p^2-16p-26=-8 | | x+2(x+2=x+16 | | -4y-16=-48 | | 16x+11+6x-3=140 | | 4+3x+6=90 | | x+29.5=61.4 | | t-(-10)=50 | | k÷(-2)+(-7)=(-11) | | 6.5g+9=3.5g+21 | | 3(x-2)=-x+2 | | 3m=9=21 | | u/5-2=-27 | | 6x+34x-7=(5x+10) | | 20+3t=92 | | 7-(-4z)=11 | | 130(x)=17.5x−10 | | 15-3x=13+x | | -v/6=-33 | | C(x)=17.5(5)−10 | | 3y—2=10 | | 7(w-85)=98 | | 5x2+6x+7=x2+-4x | | 6x^2+48x-52=0 | | 3x+5=20-0.5x | | -4(5+3x)=-30-10x+3 | | -(x-26)=x-4(1-2x | | -4-9m=-49 | | 7=s+$1.75 | | 3x+5=20-0.5 |

Equations solver categories